Local Piezoelectric Behavior of Potassium Sodium Niobate Prepared by a Facile Synthesis via Water Soluble Precursors. Issue 16 (26th February 2018) - Senes, Nina; Iacomini, Antonio; Domingo, Neus; Enzo, Stefano; Mulas, Gabriele; Cuesta‐Lopez, Santiago; Garroni, Sebastiano
Abstract : Due to the ever‐increasing restrictions connected to the use of toxic lead‐based materials, the developing of lead‐free piezoceramics has become one of the most urgent tasks. In this context, potassium sodium niobate materials (KNN) have attracted a lot of interest as promising candidates due to their excellent piezo properties. For this reason, many efforts have been addressed to optimize the synthesis process now suffering by several drawbacks including the high volatilization of potassium and sodium at the conventional high temperature treatments and the use of expensive metal precursors. To overcome these issues, a new modified Pechini method to synthesize single phase K0.5 Na0.5 NbO3 powders, from water soluble metal precursors, is presented. Microstructural and structural parameters are characterized by X‐ray diffraction (XRD). Depending on the amount of citric acid added to the starting reagents, two pure single‐phase K0.5 Na0.5 NbO3 (2 g citric acid) and K0.3 Na0.7 NbO3 (0.2 g citric acid), respectively, are obtained with a good crystallinity at a moderate temperature of 500 °C. The piezo responses of the as calcined systems are tested by piezoresponse force microscopy (PFM). K0.5 Na0.5 NbO3 exhibits a much higher response with respect to the other phase, which relates to the larger crystallinity and to the chemical composition. Abstract : Potassium sodium niobate (KNN) powders are efficiently synthesized by a versatile and cost‐effective sol‐gel method exploiting water soluble metal sources and citric acid. The systems calcined at 500 °C, are structurally characterized by X‐ray diffraction and scanning electron microscopy. The KNN system with a chemical composition K0.5Na0.5NbO3 shows a good crystallinity and a large local piezoresponse measured by Vertical piezoresponse force microscopy (VPFM).